2002
DOI: 10.1002/cncr.10473
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial comparing neoadjuvant chemotherapy with radiotherapy alone in patients with advanced nasopharyngeal carcinoma

Abstract: BACKGROUND A prospective, randomized study was performed to determine the efficacy of neoadjuvant chemotherapy over radiotherapy alone in patients with locally advanced nasopharyngeal carcinoma. METHODS From January 1991 to December 1998, 80 patients were enrolled in this study. Patients with locoregional carcinoma of the nasopharynx were randomized to receive two courses of chemotherapy, consisting of cisplatin and 5‐fluorouracil (CDDP‐5FU), that were administered before radiation therapy (CT arm) or radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(74 citation statements)
references
References 28 publications
0
73
1
Order By: Relevance
“…Perhaps, this might be related with the fact that induction chemotherapy delayed the time of radiotherapy. In 2002, Hareyama et al (Hareyama et al, 2002) reported a randomized Phase III trial comparing neoadjuvant chemotherapy followed by radiotherapy with radiotherapy alone in patients with advanced NPC. With a median follow-up of 49 months, no significant differences were found in 5-year overall survival (60% versus 48%) and 5-year disease free survival (55% versus 43%).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, this might be related with the fact that induction chemotherapy delayed the time of radiotherapy. In 2002, Hareyama et al (Hareyama et al, 2002) reported a randomized Phase III trial comparing neoadjuvant chemotherapy followed by radiotherapy with radiotherapy alone in patients with advanced NPC. With a median follow-up of 49 months, no significant differences were found in 5-year overall survival (60% versus 48%) and 5-year disease free survival (55% versus 43%).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been nine phase III randomised trials to investigate the role of combined chemoradiotherapy in NPC so far (Rossi et al, 1988;Chan et al, 1995Chan et al, , 2002Cvitkovic and INCSG, 1996;Al-Sarraf et al, 1998;Chua et al, 1998;Ma et al, 2001;Chi et al, 2002;Hareyama et al, 2002). Table 5 summarises the results.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the only randomised trial of positive results in survival analysis, its wide application to non-American NPC patients should be considered with caution. First, about 30% patients of the Intergroup study have WHO type I histology (keratinising squamous cell carcinoma), but European (Cvitkovic et al, 1996), Japanese (Hareyama et al, 2002), or Chinese (Chan et al, 1995(Chan et al, , 2002Chua et al, 1998;Ma et al, 2001;Chi et al, 2002) series usually contain less than 5% WHO type I patients. Second, the survival data of radiotherapy alone are unexplainedly low -24% 3-year progression-free survival rate and 47% 3-year overall survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were considered to have received induction chemotherapy if it was started ≥43 days before the start of RT. This time point was chosen as it would allow for administration of 2‐3 cycles of induction chemotherapy used in recent trials 7, 8, 10. Patients were considered to have received concurrent CRT if chemotherapy started within 21 days after the start of RT as this would allow for overlap of at least 2‐3 cycles of concurrent chemotherapy with RT.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, induction chemotherapy is thought to be better tolerated and may result in early eradication of micrometastasis, leading to the hypothesis that it may result in improved survival. However, this has been controversial as several studies have found a survival benefit with this approach, while others have not 8, 9, 10. A meta‐analysis based on individual patient data has showed no benefit with induction chemotherapy 11.…”
Section: Introductionmentioning
confidence: 99%